2021
DOI: 10.1177/1178633721994605
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of ACE2 Expression by Ascorbic Acid Alone and its Combinations with Other Natural Compounds

Abstract: Background: Angiotensin-converting enzyme II or ACE2 is an integral membrane protein present on many types of cells, including vascular endothelial cells and lung alveolar epithelial cells. This receptor serves as the entry point for SARS-coronaviruses (SARS-CoVs), including a novel coronavirus 2019-nCoV. Limited availability of these receptors can thwart cellular entry of this virus. Methods: We tested the effects of ascorbic acid (vitamin C) on cellular expression of ACE2 at the protein and RNA levels in hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 21 publications
4
17
0
Order By: Relevance
“…6). These findings further expand on our earlier study using SARS-CoV-2 virion particles, which identified core ingredients in this combination, which were effective in inhibiting viral binding to hACE2 receptor and decreasing expression of ACE2 receptors on human small alveolar epithelial cells [21]. Taking into account immediate availability and high safety profile of these natural compounds, their application as preventive measures, e.g.…”
Section: Discussionsupporting
confidence: 80%
“…6). These findings further expand on our earlier study using SARS-CoV-2 virion particles, which identified core ingredients in this combination, which were effective in inhibiting viral binding to hACE2 receptor and decreasing expression of ACE2 receptors on human small alveolar epithelial cells [21]. Taking into account immediate availability and high safety profile of these natural compounds, their application as preventive measures, e.g.…”
Section: Discussionsupporting
confidence: 80%
“…Overexpression of ACE2 enhances viral entry, whereas blockage with ACE2 antibody reduces SARS-CoV-2 infection (Hoffmann et al, 2020). Therefore, inhibition of ACE2 expression has been proposed as a strategy to treat COVID-19 (Ahmad et al, 2021;Ivanov et al, 2021). In contrast, ACE2, as an important component of RAS axis, exerts anti-inflammatory and antioxidative functions and maintains metabolic homeostasis as supported by our current findings.…”
Section: Discussionsupporting
confidence: 76%
“…The known actions of vitamin C indicate that it would also be a plausible adjunct treatment for COVID-19. The findings that plasma vitamin C levels are low in COVID-19 patients (Chiscano-Camon, Ruiz-Rodriguez, Ruiz-Sanmartin, Roca & Ferrer, 2020), and that vitamin C lowers expression of angiotensin converting enzyme 2, the entry point for SARS-CoV-2 into cells (Ivanov, Goc, Ivanova, Niedzwiecki & Rath, 2021), further indicate that it may have beneficial actions in COVID-19. Intravenous vitamin C (1.5-14.0 g) has been investigated in COVID-19 patients with mild beneficial effects (Jamalimoghadamsiahkali et al, 2021;Zhao et al, 2021), but the effects of mega-doses have not been studied.…”
Section: Treatment Of Covid-19 With Vitamin Cmentioning
confidence: 99%